Tsunami Modeling Study in Geological Disaster Mitigation in the Kwandang Region - Mooduto, Tirsya Aygina Jaenet; Ahmad, Fadhil Abdillah; Kodung, Mohamad Ashar Fitrayadi Ramdan S.; Sari, Ni Luh Ananda Pusvita; Hidayansya, Taufik; Permana, Aang Panji (Universitas Negeri Gorontalo, 2024)
The northern coast of the northern arm of Sulawesi is the meeting place of 3 plates that collided with each other during the Neogene period. This condition makes the northern part of Gorontalo, especially Kwandang sub-district, very prone to earthquakes with magnitudes above 6 on the Richter scale (SR), which is one of the triggers for tsunamis. In the period from 1990 - 2008, there were 4 major earthquakes recorded in Gorontalo, namely 1990 (7.3 SR), 1991 (7.1 SR), 1997 (7.0 SR) and 2008 (7.7 SR). Therefore, further research is needed on the return period of the earthquake and the tsunami model that occurs and the sign of tsunami occurrence in the past. This research aims to determine the return period of the earthquake that caused the tsunami and the tsunami model as well as the sedimentology analysis of paleotsunami deposits. The calculation of the earthquake return period uses the Guttenberg-Richter method. Modeling calculations were carried out using the COMCOT numerical model. This model performs calculations by solving shallow water equations in the form of both linear and non-linear equations. Paleotsunami deposits were analyzed using the sedimentology method. The results of the calculation at a magnitude of 6.0 SR show that within 100 years, the study area has a chance of a potentially destructive earthquake of 1.14024978. The results of modeling the tsunami-prone zone, obtained an area of 165.598389 ha. And obtained paleotsunami deposits containing foraminifera with a sediment thickness of 14 cm.